Effects of Ethanol Addition and Ba/Ti Ratios on Preparation of Barium Titanate Nanocrystals Via a Spray Pyrolysis Method - Wang, Wei-Ning; Wuled Lenggoro, I.; Okuyama, Kikuo; Terashi, Yoshitake; Wang, Yu-Cong (Journal of the American Ceramic Society, 2006)
BaTiO3 nanocrystals were synthesized by using a low‐pressure spray pyrolysis (SP) method. A new strategy was proposed to improve nanocrystal formation and phase evolution by ethanol addition and Ba/Ti molar ratio variation, respectively. A mixture of submicron and nanoparticles was found with SP of precursors without ethanol addition, while only nanoparticles could be obtained by ethanol addition. BaTiO3 crystal growth was improved by increasing the Ba/Ti ratio. In comparison, SP of the same precursor under atmospheric conditions resulted in only submicron particles with smooth surfaces and irregular morphology.